2020
DOI: 10.1007/s12274-020-3010-7
|View full text |Cite
|
Sign up to set email alerts
|

Noble-metal-free catalyst with enhanced hydrogen evolution reaction activity based on granulated Co-doped Ni-Mo phosphide nanorod arrays

Abstract: The development of noble-metal-free electrocatalysts for water splitting is indispensable for the efficient production of hydrogen fuel. Herein, a Co-doped Ni-Mo phosphide nanorod arrays fabricated on porous Ni foam was shown to be an efficient binder-free electrocatalyst for water splitting. This catalyst featured exceptional activity, exhibiting an overpotential of 29 mV at a current density of 10 mA•cm −2 for the hydrogen evolution reaction, whereas the corresponding precatalyst exhibited an overpotential o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 61 publications
(62 reference statements)
0
15
0
Order By: Relevance
“…It has been observed that the existence of two or more dopant elements also increases the potential to enhance the conductive nature, active sites, and the prospect of tuning the catalytic activity of the host material. For example, Fe–Ni incorporated conductive metal‐organic framework (CMOF) nanowire arrays on CC, [ 299 ] Fe doped Ni 3 S 2 NNs supported on NF, [ 300 ] Co‐doped Ni–Mo phosphide nanorod arrays fabricated on NF, [ 301 ] ternary pyrite‐type cobalt phosphosulfide (CoPS) on CFP, [ 302 ] vanadium doped CoP nanorods array catalyst grown on CC, [ 303 ] and electrodeposited Co–P on a CuO nanowire array on CF [ 304 ] have been realized as robust electrocatalysts for energy conversion.…”
Section: Hydrogen Evolution (Her) and Oxygen Evolution Reactions (Oer...mentioning
confidence: 99%
“…It has been observed that the existence of two or more dopant elements also increases the potential to enhance the conductive nature, active sites, and the prospect of tuning the catalytic activity of the host material. For example, Fe–Ni incorporated conductive metal‐organic framework (CMOF) nanowire arrays on CC, [ 299 ] Fe doped Ni 3 S 2 NNs supported on NF, [ 300 ] Co‐doped Ni–Mo phosphide nanorod arrays fabricated on NF, [ 301 ] ternary pyrite‐type cobalt phosphosulfide (CoPS) on CFP, [ 302 ] vanadium doped CoP nanorods array catalyst grown on CC, [ 303 ] and electrodeposited Co–P on a CuO nanowire array on CF [ 304 ] have been realized as robust electrocatalysts for energy conversion.…”
Section: Hydrogen Evolution (Her) and Oxygen Evolution Reactions (Oer...mentioning
confidence: 99%
“…Introducing foreign atoms into TMPs to form heterostructures is an effective strategy to increase active sites and enhance reaction kinetics [23,24]. For instance, incorporating Co cations into Ni 5 P 4 could generate two new phases (hexagonal NiCoP and orthorhombic CoP).…”
Section: Introductionmentioning
confidence: 99%
“…In general, doped NMPs exhibit optimized electronic structures and reaction kinetics, resulting in improved electrochemical performance compared to pristine NMPs. 33–35…”
Section: Introductionmentioning
confidence: 99%
“…In general, doped NMPs exhibit optimized electronic structures and reaction kinetics, resulting in improved electrochemical performance compared to pristine NMPs. [33][34][35] Inspired by the discussion above, an Os-doped Ni x P (Ni 2 P-Ni 12 P 5 ) nanosheet array/N-C composite on nickel foam (Os-Ni x P/N-C/NF) was constructed by growing a 2D Os-doped Ni-MOF on Ni foam followed by the phosphating process. The Ndoped carbon 2D matrix nanosheet arrays not only enhance the electrical conductivity but also anchor the Os-Ni x P particles to prevent agglomeration and expose more active sites.…”
Section: Introductionmentioning
confidence: 99%